Effect of ethanol solvents on total phenolic content and antioxidant properties of seed extracts of fenugreek (Trigonella foenum-graecum L.) varieties and determination of phenolic composition by HPLC-ESI-MS - Lohvina, Hanna; Sándor, Makai; Wink, Michael (Diversity, 2021)
Fenugreek (Trigonella foenum-graecum L.) is one of the oldest cultivated plants grown for its leaves and seeds that are used for both culinary and medicinal purpose. This study aims to evaluate the effect of ethanol concentration (30, 50, 70 and 96% (v/v) of ethanol in water) as a solvent for the extraction of total phenolic content (TPC) and antioxidant properties (antiradical activity (ARA), transition metal reducing power (TMRP), iron chelating ability (ICA)) of seed extracts of spring variety Ovari 4 (FSV) and winter variety PSZ.G.SZ (FWV) fenugreek, and separate and identify the major phenolics of the extracts by HPLC-ESI-MS. The results indicated that 70% ethanol solution resulted in the maximum amount of TPC for both FSV and FWV seeds. The TPC decreased in the treatments in the following order: 70% ethanol > 96% ethanol > 50% ethanol > 30% ethanol, whereas extraction yield changed in a different manner: 30% ethanol > 50% ethanol > 70% ethanol > 96% ethanol. The extracts from seeds of both fenugreek varieties obtained with 70% and 96% ethanol showed equal high RSA while superior TMRP and ICA were observed in 70% ethanol extracts. The TMRP and ICA were strongly correlated with TPC for both varieties. The correlation between RSA and TPC was high, but not significant. Thus, the obtained data indicate the 70% ethanol solvent suitability for efficient extraction of phenolic compounds from seeds of the FWV and FSV. According to an HPLC-ESI-MS analysis, the polyphenolic profiles of fenugreek are presumably formed by flavone C-glycosides with apigenin or luteolin as aglycone linked with different glycones. High antioxidant activity of FWV seeds can be an adaptation to cold stress of the winter variety aimed at strengthening the antioxidant defense of the germinating seeds.
Gesehen am 08.06.2022